KETERLAMBATAN PEMBERITAHUAN AKUISISI SAHAM OLEH PERUSAHAAN ASAL MALAYSIA KEPADA KOMISI PENGAWAS PERSAINGAN USAHA - Apriola Naftalie Dewani (2023)
The purpose of this paper is to analyze the impact of the delay in notification of share acquisition by a company from Malaysia for the act of taking over company shares in Indonesia and the forms of liability that can be carried out by KPPU. This research was conducted using normative juridical research. The novelty in this research refers to the explanation of the forms of responsibility carried out by the KPPU to improve the notification system in Indonesia and prevent a concentrated market structure. The results of this study indicate that the impact that can occur due to delays will be detrimental to business actors in terms of the economy and interested parties such as structural parties and financial parties. In addition, in this case, KPPU also has the responsibility to make changes to the notification regime from post notification to pre notification and to limit HGU to business entities to provide optimal supervision for KPPU so as to prevent monopolistic practices and unfair business competition.